Optimization of Tobacco Waste Extraction using Ultrasonic Assisted Extraction (UAE) to Produce Biopestiside - Safitri, Mega Desy; Wagiman, Wagiman; Jumeri, Jumeri (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Tobacco waste has the same bioactive compounds as tobacco leaves but with lower concentrations such as nicotine, phenolic compounds, aromatic substances, and solanesols. Utilization of tobacco waste that is not optimal can be processed to produce bioactive compounds that are beneficial to the surrounding environment. Tobacco waste can be processed into biopesticides containing nicotine and solanesol which function as antifungals and antioxidants. Tobacco waste was processed using the UAE maceration method using variables of temperature (40-600C), time (15-30 minutes), and type of solvent (acetone, methanol, and 96% ethanol). The results of UAE maceration were processed using Response Surface Methodology (RSM) data to determine optimal in yield, antifungal, and antioxidant activity tests. The study produced optimal values in UAE maceration, namely using a temperature of 52.470C, 29.86 minutes, and 96% ethanol solvent with a yield of 9.92%, 97.89% antifungal, and antioxidant activity (IC50) 16.75 ppm.